The Paradigmatic Approach and Models of Adult Learning in Modern Higher Education - Vykhrushch, Vira (Pedagogical Discourse, 2017)
In the article the author analyzes the andragogical approach as a methodological category of pedagogics. The approach as a methodological category is seen from the paradigm’s perspective that suggests: the andragogical approach is implemented on the basis of polyparadigmality in modern education in the context of humane pedagogics, which is the highest value of the person. The axiological mechanisms of andragogical paradigm of adult education and its models in higher education are analyzed. Andragogy is an alternative to common teaching methods and today cannot yet be presented in only one theory, model or system of principles. The concept of andragogy by M.S. Knowles begins to influence the theory and practice of primary, secondary and university education. Most domestic scholars tend to understand andragogy as an independent science and believe that the approach to andragogy as a methodological category, the science of adult education study significantly narrows its essence and capacity. M.S. Knowles compares pedagogical and andragogical models in details, but considers their negative (school / pedagogical model) and positive (andragogical model) interpretations wrongful. The basis of the comparative analysis comprises the following indicators: the need to know; the student’s Self-concept; the role of the student’s experience; willingness to learn; orientation on training; motivation. The essence of the process model is associated with the maintenance of procedures and resources that help adult learners acquire information and skills. The andragogical model is presented as a worldview, the system of alternative ideas, business model that meets the characteristics of a learning situation. Teaching becomes more effective when the teacher has adapted some andragogical ideas for pedagogical model. The contribution to the development of the problem was researched by S.O. Hall (who identified three types of adults in relation to their attitudes to goals and values of continuing their education) and A. Tough (concerning not only what and why adults learn, but how they learn and what help they need to learn). Key words: teaching paradigm, learning model, adult student, angragogy, pedagogical model, andragogical model, higher education, teaching of adults.